Wave propagation in solids : presented at ASME Winter Annual Meeting, Los Angeles, California, November 20, 1969 - Miklowtiz, Julius; American Society of Mechanical Engineers; ASME Winter Annual Meeting (1969 : Los Angeles, California) (New York : American Society of Mechanical Engineers, 1969)
40